LIMITATIONS AND POSSIBILITIES IN IMPLEMENTING THE SURGICAL SAFETY CHECKLIST - Gonçalves Maia Brasil, Eysler (2023)
Objective: To identify, through a literary collection, the possibilities and limitations in the implementation of the LVSC, by the multiprofessional team, with a focus on nursing. Method: This was na integrative literature review. The research question was “what are the limitations and possibilities in the process of implementing the LVSC, from the perspective of the nursing team, in the practice of health services?”. The search for articles was carried out between February and March 2021, through the LILACS, SciELO, BDENF, PUBMED/MEDLINE and SCOPUS databases. To search for articles, the following combinations of Decs were used: “Perioperative Nursing”; “Checklist” and “Patient Safety”. Inclusion criteria: original articles available in full in Portuguese and published from 2016 to 2021. Exclusion criteria were: duplication in databases, monographs, dissertations and theses. In total, 171 articles were found, after applying the criteria, the sample consisted of 16 articles. Result: Two categories were evidenced, presenting the characteristics of the limitations and possibilities of implementing the LVSC. Six subcategories were identified, with three limitations: lack of adherence of the multidisciplinary team; incorrect filling/omission of information; lack of professional qualification/training and three possibilities: involvement of the multidisciplinary team; qualification/training for the correct completion of the list and adaptation of the checklist. Conclusion: The data will allow a reflection on the LVSC implementation process, which consequently can contribute to the creation of strategies to face the limitations of this process, creating methods, adaptations and possibilities that will promote the adhesion of this instrument. Keywords: Perioperative nursing; Check list; Patient safety.